2015
DOI: 10.3390/ijerph120809025
|View full text |Cite
|
Sign up to set email alerts
|

Residence in Proximity of an Iron Foundry and Risk of Lung Cancer in the Municipality of Trieste, Italy, 1995–2009

Abstract: We assessed the risk of lung cancer in people living near the iron foundry located within the city of Trieste, Northeastern Italy. Between 1995 and 2009, all incident cases of lung cancer and corresponding population were considered. A deposition model of the foundry-specific emissions of SO2 defined: “nearby”, “urban”, and “outlying” areas. Rate ratios (RRs) and annual percent changes (APCs) were computed. Among nearby residents, significantly increased risks of lung cancer were noted in men below age 75 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Fourth, we assumed the residential location of the participants as a proxy of individual exposure. Our study population was relatively stable, with nearly 93% of the FVG population living in their area of residence for more than 15 years 30 .…”
Section: Discussionmentioning
confidence: 98%
“…Fourth, we assumed the residential location of the participants as a proxy of individual exposure. Our study population was relatively stable, with nearly 93% of the FVG population living in their area of residence for more than 15 years 30 .…”
Section: Discussionmentioning
confidence: 98%
“…In this study we obtained the structure of the residential population (by sex, age in quinquennia, and calendar year) using the same methodology applied in our previous investigation [ 12 ]. In the study area, 96.3% of residential addresses, extracted from regional healthcare population database between 1995 and 2009, were geocoded.…”
Section: Methodsmentioning
confidence: 99%
“…We calculated annual percent change (APC) [ 20 , 21 ] of incidence rates using Joinpoint software, for the whole 1995–2009 period in both sexes and by the two age groups (<75 and ≥75 years) according to tertile of exposures. Statistical significance ( p < 0.05) of annual APC was calculated using a Student’s t-distribution [ 12 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…This previous study provided insight for the development of lung cancer caused by PM pollution; it was hypothesized that a nearby iron foundry may influence the physical condition of local residents. Another study demonstrated that men (aged <75 years), but not women, residing within 800 m of the iron foundry coke oven had a high lung cancer risk (110).…”
Section: Iron and Various Cancersmentioning
confidence: 99%